Vibrio Anguillarum: A Comparative Study of Fish Pathogenic, Environmental, and Reference Strains - Larsen, Jens Laurits (Acta Vet Scand, 1983)
An examination of 41 fish pathogenic and 51 environmental strains of Vibrio anguillarum from Danish coastal areas, and of 8 reference strains of Vibrio anguillarum, biotype 1, showed that these strains shared rather broad-spectered activities towards many carbohydrates, amino acids, proteins and lipids. They also exhibited rather uniform growth characteristics, including parameters as salinity (NaCl), temperature, antibiotic resistance, and growth on specific media. A computer analysis of these strains and 3 strains of Vibrio anguillarum, biotype 2 (Vibrio ordalii), showed that the Danish strains all belonged to Vibrio anguillarum, biotype 1, and that no basis existed for setting up new biotypes. Mean values of the G+C content in DNA of strains of the various categories of Vibrio anguillarum, biotype 1, ranged from 45.5 to 46, while the mean value for the Vibrio ordalii strains was 48.9. The biochemically active Vibrio anguillarum seems more suitable for environmental studies than the more fastidious Vibrio ordalii.